Photochemistry of 3H-furo[3,4-c]pyrazoles and 3H-thieno[3,4-c] pyrazoles - Payne, Alan (Pergamon-Elsevier Science Ltd, 2013)
The first examples of 3H-furo [3,4-c]pyrazoles and 3H-thieno[3,4-c]pyrazoles were prepared in an attempt to isolate examples of cyclopropane-fused thiophenes and furans. Adducts of acetylenic ketones and 2-diazopropane were reacted with 10-camphorsulfonic acid or phosphorus pentasulfide to produce the title compounds. Photolysis of these compounds did not give the cyclopropane-fused products rather an unreported photochemical fragmentation was observed.